2018
DOI: 10.15361/1984-5529.2018v46n4p403-411
|View full text |Cite
|
Sign up to set email alerts
|

Pre-sprouted seedlings production methods through buds or mini-stems: Emergence and initial development of sugarcane cultivars

Abstract: This study evaluates the emergence and initial development of sugarcane cultivars with different bud sizes, based on the system of pre-sprouted seedlings (PSS). Early sugarcane cultivars (RB966928, RB855156 and IACSP91-1099) were evaluated. These evaluations comprised three positions of the sugarcane stem (tip, middle and base) and four types of sugarcane propagules (mini-stem and 3 bud sizes with different diameters: 22 mm (1), 29 mm (2) and 35 mm (3)). Three trials were performed, each with a different culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In the absence of inoculation, PSS survival of 82.4% corroborates with the results found by Almeida Neto et al [67]. Although no other studies evaluate PSS survival in the field under the use of microorganisms, studies reported the PGPB action in improving rooting and nutritional aspects [37,[68][69][70][71].…”
Section: Discussionsupporting
confidence: 86%
“…In the absence of inoculation, PSS survival of 82.4% corroborates with the results found by Almeida Neto et al [67]. Although no other studies evaluate PSS survival in the field under the use of microorganisms, studies reported the PGPB action in improving rooting and nutritional aspects [37,[68][69][70][71].…”
Section: Discussionsupporting
confidence: 86%
“…Traditionally, the planting of the crop is carried out by the distribution of culm segments (setts) with 3-4 buds in furrows or through the system of pre-sprouted seedlings (PSS) -culm cutting around the node containing one axillary bud 7 . The regulation of axillary bud outgrowth is crucial for cultures that use vegetative propagation.…”
Section: Introductionmentioning
confidence: 99%